The association between iron deficiency and muscle mass/strength in patients undergoing maintenance hemodialysis - Liu, Yan; Chen, Min; Zhang, Jieyi; Luo, Jie; Chen, Tingyu; Zeng, Xiaoyan; Nie, Huibin (Frontiers in Nutrition, 2025)
BackgroundPatients with end-stage renal disease (ESRD) are at high risk of losing muscle mass and strength, especially those undergoing maintenance hemodialysis (MHD). Iron deficiency (ID) may exacerbate this condition, however, its relationship with muscle mass/strength remains largely unclear. Therefore, we aim to investigate the association between ID status and muscle mass/strength in Chinese patients undergoing hemodialysis.MethodsThis cross-sectional study was conducted at a hemodialysis center in southwest China from September to December 2022. Iron status was assessed by plasma ferritin and transferrin saturation (TSAT). Muscle strength was measured by handgrip strength (HGS), and muscle mass was evaluated using the appendicular skeletal muscle index (ASMI). Linear regression and subgroup analysis with interaction terms were performed to explore the associations.Results269 participants on MHD aged 18–85 years were included, 21.9% (59/269) had ID. Participants with ID exhibited significantly lower handgrip strength, but similar ASMI, compared to those without ID (grip strength: 21.6 ± 8.7 vs. 24.3 ± 8.9, ASMI: 6.5 ± 1.2 vs. 6.5 ± 1.0). After adjusting for potential covariates, ID was negatively associated with handgrip strength (β = −2.21, 95% CI: −4.08 to −0.34, p = 0.021). Subgroup analysis confirmed the stability of this result. Interestingly, when stratified by overweight status, ID was significantly associated with ASMI in overweight participants (β = 0.50, 95% CI: 0.17–0.84, p = 0.004), while no association was observed in non-overweight participants (β = −0.20, 95% CI: −0.44 to 0.05, p = 0.240; p-value for interaction = 0.004).ConclusionThese findings demonstrate that ID is significantly associated with reduced muscle strength in patients on MHD in southwest China. Additionally, ID was significantly associated with muscle mass only in overweight participants. These results provide strong support for the importance of individualized iron—repletion strategies to preserve muscle health in patients on MHD, particularly those who are overweight, although further verification in prospective studies is needed.